PENGARUH KINERJA DAN TAMPILAN ALAT FERTIGASI TANAMAN VANILI “FELOVA” TERHADAP MINAT PENGGUNA: the influence of performance and appearance of the "felova" vanilla plant fertigation tool on user interest - Saragih, Bennefit Christy; Hikmah Rahmah; Nur Aziezah; Bayu Widodo; Irmansyah (Jurnal Sains Terapan : Wahana Informasi dan Alih Teknologi Pertanian, 2024)
Tool functionality and appearance are important factors in determining whether Felova products are worth using to assist in watering and applying fertilizer to vanilla plants. Products with the best performance and appearance will increase efficiency and help users achieve optimal vanilla yields. Felova is an automated fertigation and irrigation tool. This survey was conducted to determine whether the performance and appearance of the Felova tool significantly influence the interest in using digital technology for vanilla plantations. Sample data was collected through questionnaires to 20 respondents of IPB University Vocational School students at the IT Festival 2023 event. This study utilizes a multiple linear regression analysis approach to test the impact of three variables, namely tool performance (X1) and tool appearance (X2) as independent variables, while user interest (Y) acts as the dependent variable. The analysis of multiple linear regression showed that the parameter value for variable X1 was -0.271 with a significance value of 0.280. The parameter value for variable X2 is 0.087 with a significance value of 0.731. Both significance values are compared with an alpha value of 5%. Furthermore, the results showed that neither the overall performance nor the appearance of the Felova tool significantly influenced user interest. The value of the coefficient of determination shows 0.070, which means that the performance and appearance of the tool can explain the user interest variable by 7% and the remaining 93% is affected by other factors outside the model.